Taxonomic revision and molecular phylogeny of the fig wasp genus AnidarnesBouček, 1993 (Hymenoptera: Sycophaginae). (17th January 2013) - FARACHE, FERNANDO H. A.; CRUAUD, ASTRID; GENSON, GWENAËLLE; PEREIRA, RODRIGO A.S.; RASPLUS, JEAN‐YVES
Abstract : Besides the pollinators (Agaonidae), several chalcidoid lineages of nonpollinating fig wasps are strictly dependent on Ficus (Moraceae) for reproduction. Overall, nonpollinating fig wasps have not received much consideration. Reliable phylogenetic and taxonomic frameworks are lacking for most groups, which hampers progress in our understanding of the evolution and functioning of fig wasp communities. Here we focus on Anidarnes Bouček (Sycophaginae), a member of the Neotropical fig wasp community. We present a detailed morphological analysis as well as the first molecular phylogeny of the genus inferred from two nuclear and two mitochondrial genes ( Cytb, COI, EF‐1α and 28S rRNA, 3937 bp). Twelve species are recognised, illustrated and a key to their identification is provided. Of those, only three were previously described and are redescribed here: A. bicolor (Ashmead); A. globiceps (Mayr) and A. brevicauda Bouček. In addition, nine new species are described: Anidarnes brevior sp.n . Farache & Rasplus (Costa Rica); A. dissidens sp.n. Farache & Rasplus (Brazil); A. gracilis sp.n. Farache & Rasplus (Costa Rica); A. isophlebiae sp.n. Farache & Rasplus (Costa Rica); A. jimeneziae sp.n. Farache & Rasplus (Costa Rica); A. longiscutellum sp.n. Farache & Rasplus (Brazil); A. martinae sp.n. Farache & Rasplus (U.S.A., Florida); A. nigrus sp.n. Farache & Rasplus (Colombia) and A. rugosus sp.n. Farache & Rasplus (Brazil). Finally, phylogenetic relationships inferred using parsimony, bayesian and maximum likelihood methods are discussed in the light of our morphological observations and the host fig tree taxonomy.